Land-cover changes and its impacts on ecological variables in the headwaters area of the Yangtze river, China - Wang, Genxu; Wang, Yibo; Kubota, Jumpei (Environmental Monitoring and Assessment, 2006)
Land cover changes affect ecological landscape spatial pattern, and evolving landscape patterns inevitably cause an evolution in ecosystem functionality. Various ecological landscape variables, such as biological productivity (plant biomass and stock capacity), soil nutrients (organic matter and N content) and water source conservation capacity are identified as landscape function characteristics. A quantitative method and digital model for analyzing evolving landscape functionality in the headwaters areas of the Yangtze River, China were devised. In the period 1986-2000, patch transitions of the region's evolving landscapes have been predominantly characterized by alpine cold swamp meadow, with the highest coverage tending to be steppified meadow or steppe, and desertification landscape such as sand and bare rock land expansion. As the result of such changes, alpine swamp areas decreased by 3.08 x 10(3)km(2)and the alpine cold sparse steppe and bare rock and soil land increased by 6.48 x 10(3) km(2) and 5.82 x 10(3)km(2), respectively. Consequently, the grass biomass production decreased by 2627.15 Gg, of which alpine cold swamp meadows accounted for 55.9% of this loss. The overall stock capacity of the headwaters area of the Yangtze River decreased by 920.64 thousand sheep units, of which 502.02 thousand sheep units decreased in ACS (Alpine cold swamp) meadow transition. Soil organic matter and N contents decreased significantly in most alpine cold meadow and swamp meadow landscape patches. From 1986 to 2000 the total losses of soil organic matter and total N in the entire headwaters region amounted to 150.2 Gkg and 7.67 Gkg. Meanwhile, the landscape soil water capacity declined by 935.9 Mm(3), of which 83.9% occurred in the ACS meadow transition. In the headwater area of the Yangtze River, the complex transition of landscape resulted in sharp eco-environmental deterioration. The main indication for these changes involved the intensity of the climate in this region is becoming drier and warmer, resulting in a ...